Serum Uric Acid and Nitric Oxide Levels in Relation to Coronary Artery Occlusion Severity in STEMI (ST Elevation Myocardial Infarct): A Meta-Analysis - Oetama, Rizqi Aulia; Iin Aulia Ernovina; Amly Aulia Permadi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Serum uric acid (SUA) and nitric oxide (NO) are implicated in cardiovascular disease pathogenesis. However, their relationship with the degree of coronary artery occlusion in STEMI patients remains unclear. We aimed to synthesize available evidence on the association between SUA, NO levels, and coronary artery occlusion severity in STEMI. Methods: We conducted a systematic search of PubMed, Embase, and Cochrane Library databases from 2018 to 2024 for studies reporting SUA and NO levels in STEMI patients undergoing percutaneous coronary intervention (PCI). We extracted data on occlusion severity (e.g., thrombolysis in myocardial infarction [TIMI] flow grade) and performed a meta-analysis using random-effects models. Results: Ten studies involving 2515 STEMI patients were included. The pooled analysis revealed a significant positive association between SUA levels and a higher degree of coronary artery occlusion (standardized mean difference [SMD] = 0.35, 95% confidence interval [CI] 0.12-0.58, p = 0.003). Conversely, NO levels were significantly lower in patients with more severe occlusion (SMD = -0.28, 95% CI -0.45 to -0.11, p = 0.001). Conclusion: Elevated SUA and reduced NO levels are associated with increased coronary artery occlusion severity in STEMI patients. These findings highlight potential therapeutic targets for improving outcomes in STEMI.